KEPUASAN KERJA - KARAKTERISTIK PEKERJAAN, PENGATURAN KERJA YANG FLEKSIBEL, DAN KESEIMBANGAN KEHIDUPAN KERJA BERDAMPAK PADA KEPUASAN KERJA DI ANTARA PARA PEKERJA KANTOR AKUNTAN PUBLIK - Budianto, Erin; Purba, Sylvia Diana (Jurnal Akuntansi, 2025)
The purpose of this research was to determine the influence of job characteristics (“JCM”), flexible work arrangements (“FWA”), and work-life balance (“WLB”) on job satisfaction (“JS”) of Public Accounting Firm (“KAP”) workers in DKI Jakarta and its surrounding areas (“Jabodetabek”). Apart from that, this research also aimed to determine the mediating role of work-life balance on job characteristics and flexible work arrangements' influence on job satisfaction. This research was conducted by surveying 123 KAP workers in the Jabodetabek area who are currently and/or have worked with FWA and have worked at KAP for at least a year. This research uses a non-probability sampling method—purposive sampling, with a convenience sampling technique. JCM has a significant positive influence on WLB and JS, both directly and through WLB mediation. Meanwhile, FWA does not have a significant positive influence on WLB and JS, either directly or through WLB mediation. JCM significantly increases JS and WLB for KAP workers. JCM can also be more potent in improving JS directly, compared to through WLB mediation. However, the most significant variable that can increase job satisfaction of KAP workers is WLB. Therefore, KAP management should emphasize and pay more attention to the WLB of their workers and the JCM of their work, including the JCM dimensions of KAP work. This research provides an explanation of the influence of the research variables JCM, FWA, WLB, and JS , where currently, no research has provided results on the influence of these variables on similar related research subjects.